Prevalence and degree of parasitation by enteric flagelates in mice nmri, C57Bl/6 and Balb/c (Gaceta de Ciencias Veterinarias, 2016)
In order to analyze the prevalence and parasitation degree by enteric flagellates in NMRI, C57Bl/6 and Balb/c mice, discriminating on the basis of strain, age and sex of animals produced conventionally in animal facilities of the Universidad Centroccidental Lisandro Alvarado (Venezuela), 50 mice were selected by strain and sex, and 10 by age (3, 5, 7, 9 and 14 weeks) (N = 300). They were sampled both fresh feces and intestinal contents at three differents sections (duodenum, yeyuno-ileon and cecum), for direct observation and smears stained with Giemsa. The data was analyzed with Chi-square, Mann-Whitney, Kruskal-Wallis test, correlation of Spearman and factor analysis. Giardia muris was located at cecum of NMRI mice (100%) and 99% of C57Bl/6 and Balb/c. At yeyuno-ileon in 89% of C57Bl/6, 84% of NMRI and 46% of Balb/c; and at duodenum, in male C57Bl/6 (73%), which increases the prevalence with age. Trichomonas muris was identified in 58-76% of the three strains with the highest prevalence in males NMRI and C57B1/6. Spironucleus muris, only 70% of the six-weeks-old NMRI were identified. The less parasitized strain is the Balb/c. There are significant differences in the prevalence of three parasitic diseases among the strains studied, about Giardia there are differences between the ages in the NMRI and C57Bl/6 and about Trichomonas between both sex. It is recommended to consider animals strain produced and/or used in research, their sex and age in order to establish the sanitary controls aimed to enteric flagellates.
Keywords: Giardia muris; Trichomona muris; Spironucleus muris; C57Bl/6; Balb/c